Modification of bile acids metabolism with multi-strain probiotic in patients with diarrhea predominant irritable bowel syndrome: a randomized study - Neverovskyi , Artem; Polishchuk , Serhii (The Ukrainian Scientific Medical Youth Journal, 2023)
one of the irritable bowel syndrome with diarrhea (IBS-D) mechanisms of development is bile acids (BA) malabsorption (BAM). The promising new therapeutic approach for BAM – probiotic bacteria producing bile salt hydrolase (BSH). The aim of the study was to compare the effect of multi-strain probiotic and cholestyramine combination with cholestyramine monotherapy on modifying the parameters of BA metabolism in IBS-D patients. Materials and methods. The trial was conducted as a randomized, open, parallel study and included 108 patients with IBS-D divided into 2 groups: case group (n=57) that received combination of probiotic (L. rhamnosus, L. plantarum, S. thermophilus, L. acidophilus, B. bifidum, B. longum, B. infantis, S. boulardii) with cholestyramine, and control group (n=51) that received cholestyramine monotherapy during 12 weeks. The total relative activity (RA) of gut bacterial BSH, serum BA (sBA) and fecal BA (fBA) were assessed in all patients. Results: total, primary and secondary sBA and fBA, proportions of primary and secondary fBA were significantly different after 12 weeks within each group comparing to baseline, p<0.05. In case group the proportions of primary and secondary sBA, RA of gut bacterial BSH were significantly different after 12 weeks comparing to baseline, p<0.05. All the parameters of BA metabolism except absolute levels of secondary sBA were significantly different after 12 weeks between the control and case groups, p<0.05. Conclusions: combination of cholestyramine and multi-strain probiotic led to more pronounced alterations of BA metabolism and increasing of gut bacterial BSH-activity comparing to cholestyramine monotherapy. It may explain possible mechanism of action of probiotics in patients with IBS-D and assumed BAM.